A multi-faceted hospital-based intervention for intrapartum care in sub-Saharan Africa: a stepped-wedge cluster-randomized trial - Claudia Hanson; Joseph Akuze; Kristi Sidney Annerstedt; Helle Mölsted Alvesson; Sunjuri Sun; Manuela Straneo; Nicola Orsini; Lenka Benova; Mechthild M. Gross; Bruno Marchal; Rian Snijders; Effie Chipeta; et al. (Nature Medicine, 2026)
Abstract Around three million babies are stillborn or die shortly after birth each year worldwide, underscoring a persistent and unacceptable burden on families and health systems. To help address this challenge, we developed the facility-based, multi-faceted Action Leveraging Evidence to reduce perinatal Mortality and Morbidity (ALERT) intervention. ALERT promoted essential practices of intrapartum childbirth using (i) co-design, (ii) training, (iii) quality improvement and (iv) leadership mentoring. We evaluated ALERT using a stepped-wedge cluster-randomized trial with five 6-month periods across 16 hospitals in Benin, Malawi, Tanzania and Uganda. Among 134,630 women (including 139,300 neonates), the intervention was associated with 22% lower odds of the composite co-primary outcome, early perinatal mortality, defined as fresh stillbirth and 24 h neonatal mortality (adjusted odds ratio 0.78, 95% confidence interval 0.65–0.94), but not with the co-primary outcome, fresh stillbirth (adjusted odds ratio 0.88, 95% confidence interval 0.68–1.13). Despite the limitation of only including 16 hospitals, the diversity of settings across four sub-Saharan African countries supports the finding that early perinatal mortality and morbidity could be reduced through implementation of multi-faceted, context-specific strategies to build maternity provider capacities. Pan African Clinical Trial Registry: 202006793783148 .